2022
DOI: 10.1002/jgf2.571
|View full text |Cite
|
Sign up to set email alerts
|

The experience of providing end‐of‐life care at home: The emotional experiences of young family physicians

Abstract: Background: End-of-life care is now a major issue in Japan as a result of the rapidly aging population; hence, the need for fostering family physicians to be engaged in end-of-life care at home is increasing. Studies in the United States and the United Kingdom have shown that physicians feel emotional and moral distress in end-of-life care, and that they develop detachment and dehumanizing attitudes toward patients as a coping mechanism. However, few studies have explored the emotional experiences that family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Previous studies have shown that uncertainty in end‐of‐life care leads to anxiety and stress among healthcare professionals, 18 , 19 which is consistent with the present study. With regard to the communication difficulties with patients and families when providing care at the end‐of‐life, studies have shown challenges in communicating about prognosis 20 and problems in dealing with diverse family opinions about patients' wishes, 21 which are generally consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that uncertainty in end‐of‐life care leads to anxiety and stress among healthcare professionals, 18 , 19 which is consistent with the present study. With regard to the communication difficulties with patients and families when providing care at the end‐of‐life, studies have shown challenges in communicating about prognosis 20 and problems in dealing with diverse family opinions about patients' wishes, 21 which are generally consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The stories of 20 family physicians who care for patients with medical needs related to social inequity highlights how moral distress can be grounded in broader systemic and structural factors. The study findings, to our knowledge, are some of the first to illustrate the moral distress experiences of family physicians, particularly those working with patients experiencing inequities, which builds upon the small body of moral distress scholarship in the primary care literature (63)(64)(65)(66)(67)(68)(69). Our participants' moral distress was associated with remuneration structures and workload demands, and was exacerbated by a lack of social resources such as housing, sufficient and comprehensive mental health and addictions services, which resulted in strict limitations on their ability to provide comprehensive care.…”
Section: Discussionmentioning
confidence: 81%